Effect of corrugation angle on the thermal behaviour of power-law fluids during a flow in plate heat exchangers - Fernandes, Carla S. (2011)
Local and average Nusselt numbers of power-law fluids were studied on PHE channels with different corrugation angles, being the effect of the temperature on viscosity also considered on the thermal correlations development.